Non-Imaging Acoustical Properties in Monitoring Arteriovenous Hemodialysis Access. A Review - Anas Mohd Noor (Institute for Research and Community Services, Institut Teknologi Bandung, 2015)
The limitations of the gold standard angiography technique in arteriovenous access surveillance have opened a gap for researchers to find the best way to monitor this condition with low-cost, non-invasive and continuous bedside monitoring. The phonoangiography technique has been developed prior to these limits. This measurement and monitoring technique, associated with intelligence signal processing, promises better analysis for early detection of hemodialysis access problems, such as stenosis and thrombosis. Some research groups have shown that the phonoangiography technique could identify as many as 20% of vascular diameter changes and also its frequency characteristics due to hemodialysis access problems. The frequency characteristics of these acoustical signals are presented and discussed in detail to understand the association with the stenosis level, blood flows, sensor locations, fundamental frequency bands of normal and abnormal conditions, and also the spectral energy produced. This promising technique could be used in the near future as a tool for pre-diagnosis of arteriovenous access before any further access correction by surgical techniques is required. This paper provides an extensive review of various arteriovenous access monitoring techniques based on non-imaging acoustical properties.